A comparative study of structural parameters of a RCC T-girder bridge using loading pattern from different codes - Sigdel, Sulav (Journal of Engineering Issues and Solutions, 2021)
Nepal is an under-developed country; it is on the threshold of becoming a developing country. With new highways and railroad projects launching, construction of bridges is likely to increase. Bridges improve connectivity across the country and provide support to the country's overall economic growth. While designing a bridge, concrete properties, reinforcement properties, superstructure and substructure sections, traffic movements and loading conditions are specified. Bridges in Nepal are designed based on criteria enumerated by Indian Road Congress (IRC) code provisions. But, there are different bridge design codes used by different countries. Although these provisions follow the same basic principles, they may yield different results. The study on various structural parameters' variation is significant while selecting the code provision for the design and analysis of the bridge. In this study, a T-Girder Bridge is considered and is modelled and analyzed by vehicular loading patterns from IRC Codal Provision, AASHTO Codal Provision, and Chinese Codal Provision. This study uses CSiBridge computer software to perform the analysis.